Significance of heterozygosis M34T mutation of GJB2 gene in non-syndromic congenital deafness. Retrospective analysis of 12,472 samples of amniotic fluid - Coco, Manuela (Journal of prenatal medicine, 2013)
OBJECTIVE: to determinate the role of heterozygosis of M34T mutation of GJB2 gene in non syndromic congenital deafness